РИВОЖЛАНГАН МАМЛАКАТЛАРДА ЎҚИТУВЧИЛАРНИНГ МАЛАКАСИНИ ОШИРИШ ТИЗИМИ: ЮТУҚ ВА КАМЧИЛИКЛАР - Турекеева, А. (SCIENCE and SOCIETY, 2019)
The author of the article discusses teachers’ qualifications upgrading in the developed countries, their success and disadvantages. It also explains that today’s primary task is not only to inculcate the knowledge and skills that students are endowed with, but first of all, the ability to absorb and practise new knowledge throughout their lives.